2022
DOI: 10.3390/ijms232012391
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and Serum Metabolic Profile Changes in Korean Native Hanwoo Steer in Response to Diet Feeding Systems

Abstract: The diversity of bacteria and their function in cattle gastrointestinal tracts can influence animal welfare. Next-generation sequencing (NGS) was used to investigate microbial diversity in the feces of Hanwoo steers reared under natural grazing (GS) and housing (HS) systems. Additionally, serum metabolic parameters, such as liver and kidney markers and mineral and lipid content changes, as well as their correlation with pyrotags, were studied. A total of 6468 ± 87.86 operational taxonomic units (OTUs) were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Rumen is an important digestive organ for ruminants, and has a wide range of rumen microbes that are extremely sensitive to feeding strategies. The feeding strategy affects the ruminal fermentation of yaks and alters the core bacterial diversity ( Dai et al, 2022 ) and also has a considerable impact on the fecal microbiota at the phylum and family levels of Hanwoo steers ( Jung et al, 2022 ). There were significant differences in bacterial composition and the concentration of ruminal VFAs (especially propionate and butyrate) in Tibetan Gangba sheep fed by different feeding strategies ( Jize et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rumen is an important digestive organ for ruminants, and has a wide range of rumen microbes that are extremely sensitive to feeding strategies. The feeding strategy affects the ruminal fermentation of yaks and alters the core bacterial diversity ( Dai et al, 2022 ) and also has a considerable impact on the fecal microbiota at the phylum and family levels of Hanwoo steers ( Jung et al, 2022 ). There were significant differences in bacterial composition and the concentration of ruminal VFAs (especially propionate and butyrate) in Tibetan Gangba sheep fed by different feeding strategies ( Jize et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have found that in both house-feeding and grazing strategies, house-feeding improved rumen development and increased the production of yak rumen acetate, propionate, and microbial protein, but the rumen bacterial and microbial richness was lower in the house-feeding yaks than in grazing yaks ( Xu et al, 2021 ; Huang et al, 2021 ; Fang et al, 2015 ). In addition, it has been shown that feeding strategy has an effect on serum metabolism, antioxidant capacity, and immunity of cattle ( Zhang, Wang & Guo, 2021 ; Jung et al, 2022 ). Polyphenolic compounds in grazing forage has been found to enhance the immunity capacity and inflammatory response in yaks, as well as improve their antioxidant capacity ( Cui et al, 2016a ).…”
Section: Introductionmentioning
confidence: 99%